Strategic Alliances Between Small or Medium-Scale Agribusiness Enterprises and Large Corporations - Nerlita Masajo-Manalili, (Asian Academy of Management Journal, 1999)
Today's environment is characterized by dynamic change and technological breakthroughs where business organizations, small and large alike, find themselves in a game with fast-changing rules. Market behavior, for instance, has change as people across geographical areas and of varying cultures now clamor for homogeneous products, when not too long ago their product preferences were highly differentiated. This homogenization of product preferences is fueled by technical breakthroughs such as sophisticated communication and transport facilities that, in turn, enhance the mobility of the factors of production (Shapiro, 1992)